Students’ Perceptions of the Use of Asynchronous Discussion Forums, Quizzes, and Uploaded Resources - Shida, Nurul; Osman, Sharifah; Halim Abdullah, Abdul (International Journal of Engineering and Technology, 2018)
This research inspects studentsâ€™ perceptions of the utilisation of asynchronous discussion forums, quizzes, and uploaded resources in platform CIDOS LMS among polytechnic students. There has been an expansion in the utilisation of LMS in many levels of education in polytechnic institutions. CIDOS LMS has variety tools examples assignments, video, scorm, and tutorial. Purposive sampling was used to choose the research participants for this study. The participants consisted of 60 diploma students from Polytechnic Sultan Ibrahim who are enrolled in a Mathematics course. The Cronbachâ€™s alpha of the instruments is 0.899. The questionnaire was divided into four categories. The categories addressed studentsâ€™ perceptions of CIDOS LMS tools, namely the discussion forums, quizzes, and the utilisation of uploaded resources. Likert scale rated from strongly disagree to strongly agree. All the data were analysed using IBM Statistical to obtain the percentages, frequencies, means, standard deviations, independent sample t-test, and Pearson correlation. The results of this study show that the practice of CIDOS LMS among engineering students at Polytechnic Sultan Ibrahim is at a high level during the learning process. Further research would explore the educatorsâ€™ need to figure out the best ways in CIDOS LMS to engage students as the millennial generation continues to dominate the workforce.Â Â